Исследовательский метод – один из способов самостоятельной познавательной деятельности ученика - Дусенбина, М.Ж. (My University, 2016)
Nowadays when there is increased requirements for any specialist, regardless of the scope of its activities, the demand for educated person owns a certain cultural level and language competence.Research methods as an educational technology performs a very important function.Firstly,it aims to ensure mastery of the methods of scientific knowledge in the search for these methods and their application. Secondly, it forms the features of creative activity. Third, it is the condition for the formation of interest. Fourth, the research method gives a full, well-informed, fast and flexible use of knowledge. The development of research skills of students helps to achieve certain objectives: to raise students' interest in learning and thereby increase the effectiveness of learning. Today’s relevant phrase is «Who owns the information, owns the world." Perhaps therein lies the main understanding of existing experience of school education. The school of knowledge is the school of four main skills development, which are listening, speaking, reading and writing. The school of personal development is the vector of translational motion, and not at the expense of denying the preceding stage, but by its absorption, development and movement forward. Research technology allows realization of student-centered approach to learning and selfmotivation. The research approach in the classroom is the necessary component of modern pedagogy. Research activity is good because it is very different by form, content, the nature of activities, number of participants, and the duration of the completion.
Keywords: research; search.; development; activity; and training